2022
DOI: 10.1186/s12903-022-02237-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the association between oral health literacy and oral health-related quality of life in older adults

Abstract: Background Poor oral health affects quality of life; oral health literacy studies are increasing as it plays an essential role in promoting oral health. However, little is known regarding the gender differences in oral health literacy and oral health-related quality of life (OHRQoL) among older adults. This study aimed to explore the gender differences in oral health literacy and OHRQoL among community-dwelling older adults in Taiwan. Methods A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Analyzing OHRQoL scores, which represent a person’s degree of well-being, is helpful for determining the potential effects of oral problems [ 29 ]. OHRQoL is a self-reported indicator of a patient’s current and recent health.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing OHRQoL scores, which represent a person’s degree of well-being, is helpful for determining the potential effects of oral problems [ 29 ]. OHRQoL is a self-reported indicator of a patient’s current and recent health.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also indicated that oral diseases in older people may cause mental impairment ( 20 ), such as cognitive decline ( 21 ), emotional challenges ( 22 ), and reduced daily activities ( 23 ). Rouxel et al noted that oral health was an individual risk factor for loneliness in older people, including oral diseases and tooth losses, which significantly influences the quality of life and wellbeing among older people ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lower OHRQoL may negatively impact eating, speaking, daily life, and social interaction [ 17 ]. Lower OHRQoL is also associated with younger age [ 18 ], being man [ 19 ], lower educational level [ 20 ], less social economic status [ 21 ], more dental caries, more severe periodontal disease, poor oral hygiene care [ 22 ], poor health status [ 23 ], and psychological impairment [ 24 ]. The biopsychosocial model for OHRQoL proposed by Wilson and Cleary [ 25 ] and Ferrans [ 26 ] posits that unfavorable personal characteristics, environmental factors, physical, social, and psychosocial functioning generate negative health perceptions and result in worse OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…According to this model, we propose that OHRQoL is affected by personal characteristics (educational level), environmental factors (annual family income), physical (chronic disease and oral health status), social, and psychosocial functioning (anxiety and BQD). Of the few studies that have explored this topic, most have researched populations in Western Asia [ 10 , 11 ], northern India [ 24 ], South Asia [ 12 ], older adults [ 18 , 19 , 21 ], and patients with diabetes [ 23 ]. Therefore, the aims of this study are, in BQ users receiving oral mucosal screening, (1) to investigate the levels of oral health, anxiety, BQD, and OHRQoL; and (2) to examine the factors (e.g., educational level, annual family income, chronic disease, oral health status, anxiety, and BQD) associated with OHRQoL.…”
Section: Introductionmentioning
confidence: 99%